Stability of mismatch negativity event‐related potentials in a multisite study. Issue 2 (30th March 2020) - Roach, Brian J.; Hamilton, Holly K.; Bachman, Peter; Belger, Aysenil; Carrión, Ricardo E.; Duncan, Erica; Johannesen, Jason; Kenney, Joshua G.; Light, Gregory; Niznikiewicz, Margaret; Addington, Jean; Bearden, Carrie E.; et al.
Abstract: Objectives: Mismatch negativity (MMN), an auditory event‐related potential sensitive to deviance detection, is smaller in schizophrenia and psychosis risk. In a multisite study, a regression approach to account for effects of site and age (12–35 years) was evaluated alongside the one‐year stability of MMN. Methods: Stability of frequency, duration, and frequency + duration (double) deviant MMN was assessed in 167 healthy subjects, tested on two occasions, separated by 52 weeks, at one of eight sites. Linear regression models predicting MMN with age and site were validated and used to derive standardized MMN z ‐scores. Variance components estimated for MMN amplitude and latency measures were used to calculate Generalizability (G) coefficients within each site to assess MMN stability. Trait‐like aspects of MMN were captured by averaging across occasions and correlated with subject traits. Results: Age and site accounted for less than 7% of MMN variance. G ‐coefficients calculated at electrode Fz were stable (G = 0.63) across deviants and sites for amplitude measured in a fixed window, but not for latency (G = 0.37). Frequency deviant MMN z ‐scores averaged across tests negatively correlated with averaged global assessment of functioning. Conclusion: MMN amplitude is stable and can be standardized to facilitate longitudinal multisite studies of patients and clinical features.